PENYULUHAN PENDAMPINGAN PEMBENTUKAN KOPERASI PADA KOMUNITAS MUDA DI JAKARTA BARAT - Caturida Meiwanto Doktoralina; Lestari Lestari; Sigit Mareta; Agusman Nurhidayat (Jurnal Pengabdian Masyarakat Ilmu Keguruan dan Pendidikan (JPM-IKP), 2024)
The objective of community service activities (PkM) is to raise awareness about the significance of comprehending the procedures for establishing cooperatives in line with Indonesian legislation. These initiatives target the youth community residing in RW 010, Kebun Jeruk, West Jakarta. Throughout the PkM activities, various methods such as didactic questioning, explicit teaching, practice and drill, and demonstrations are employed, and Q&A sessions gauge the participants' grasp of the cooperative formation process. The reseult of this Programme, the community recognises the importance of acquiring knowledge in founding cooperatives according to the Republic of Indonesia Law No. 25/1992, integrating information technology as a model for sustainable economic empowerment.